2013
DOI: 10.1093/ije/dyt180
|View full text |Cite
|
Sign up to set email alerts
|

Profile: The Mbita Health and Demographic Surveillance System

Abstract: The Mbita Health and Demographic Surveillance System (Mbita HDSS), located on the shores of Lake Victoria in Kenya, was established in 2006. The main objective of the HDSS is to provide a platform for population-based research on relationships between diseases and socio-economic and environmental factors, and for the evaluation of disease control interventions. The Mbita HDSS had a population of approximately 54 014 inhabitants from 11 576 households in June 2013. Regular data are collected using personal digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Table 5.3 summarises characteristics of 6640 inhabited houses of which information about the house was collected. These results are comparable to other HDSSs in Western Kenya, such as Asembo and Gem (Odhiambo et al, 2012) and around Mbita (Kaneko et al, 2012;Wanyua et al, 2013). On Rusinga a typical house is made from mud walls, a roof of iron sheeting with a cement floor.…”
Section: Key Findingssupporting
confidence: 79%
See 2 more Smart Citations
“…Table 5.3 summarises characteristics of 6640 inhabited houses of which information about the house was collected. These results are comparable to other HDSSs in Western Kenya, such as Asembo and Gem (Odhiambo et al, 2012) and around Mbita (Kaneko et al, 2012;Wanyua et al, 2013). On Rusinga a typical house is made from mud walls, a roof of iron sheeting with a cement floor.…”
Section: Key Findingssupporting
confidence: 79%
“…Thus where traditional paper based HDSSs would approximately use one A4 for updates on household information and one A4 for individual health information, a digitalized data collection with 25,000 people and 8,000 houses would save over 30,000 A4 papers per survey. In the last five years there are sites where HDSSs have migrated from paper-based to some sort of digitalized entering system (Kouanda et al, 2013;Odhiambo FO, 2012;Sacoor et al, 2013;Sifuna et al, 2014;Wanyua et al, 2013). However, none of these sites have linked data collection software in the field directly to a real-time database.…”
Section: Resource Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…A stream of publications from population surveillance sites reflects the match between population health approaches and the health systems research approach (68). Given the need to compare alternative programme intervention models using a population health perspective, PRRINN-MNCH undertook to launch a Health and Demographic Surveillance System (HDSS) site.…”
mentioning
confidence: 99%
“…Data on perceived susceptibility and severity of malaria were readily available because studies from the area Wanyua, Ndemwa et al 2013) showed that residents regarded malaria as a major threat to life, especially for children. We therefore concentrated on perceived benefits and barriers of adhering to recommended behaviours to ensure proper deployment of SMoTS.…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%